2016
DOI: 10.1590/1983-21252016v29n221rc
|View full text |Cite
|
Sign up to set email alerts
|

METHODS FOR OVERCOMING SEED DORMANCY AND THE INITIAL GROWTH OF Ziziphus joazeiro Mart. IN DIFFERENT SOILS

Abstract: -Considering the potential and importance of biodiversity of the Caatinga biome, studies on endemic species are relevant to conservation of its natural resources. The objectives of this work was to evaluate seed viability and physical methods for overcoming seed dormancy in juazeiro (Ziziphus joazeiro Mart.) and assess the influence of different types of soil on the initial growth of juazeiro plants. The experiments were conducted in three stages. In the first stage, the viability of seeds from different lots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(13 reference statements)
0
2
0
2
Order By: Relevance
“…This occurrence of Z. joazeiro in the coastal region can be explained by the great capacity that some species of the Caatinga must adapt to disturbed environments (with vegetation removed), thus being able to call them "ruderal". According to Costa et al (2016b), the species has a high potential to develop in different environments, adapting well to soils with different textures and chemical compositions. Thus, the abundance of Z. joazeiro in the transition areas may have allowed the species to use this plasticity to colonize new areas, especially in environments with no competition from Atlantic Forest species.…”
Section: Resultsmentioning
confidence: 99%
“…This occurrence of Z. joazeiro in the coastal region can be explained by the great capacity that some species of the Caatinga must adapt to disturbed environments (with vegetation removed), thus being able to call them "ruderal". According to Costa et al (2016b), the species has a high potential to develop in different environments, adapting well to soils with different textures and chemical compositions. Thus, the abundance of Z. joazeiro in the transition areas may have allowed the species to use this plasticity to colonize new areas, especially in environments with no competition from Atlantic Forest species.…”
Section: Resultsmentioning
confidence: 99%
“…These results corroborate the findings of Trovão et al (2007) which confirming that this species has phenotypic plasticity for adaptations to water stress. Likewise, Souza et al (2015) have shown that species that remain always green throughout the year, such as Z. joazeiro, exhibit a set of foliar functional traits related to the drought tolerance strategy, adapting to different textures of soils and chemical compositions (Costa, Silva, Coelho, Santos, & Seabra, 2016).…”
Section: Plant Growthmentioning
confidence: 99%
“…O Ziziphus joazeiro, conhecido popularmente como juá, juazeiro, é endêmico da caatinga, e possui uma grande resistência a períodos de seca devido ao seu desenvolvimento radicular complexo. O desenvolvimento dessa planta é lento, com dificuldade na germinação das sementes, o que compromete a sobrevivência da espécie, uma vez que a atividade humana desenfreada na região ocasiona problemas no seu ecossistema (COSTA et al, 2016). É encontrada principalmente no Nordeste do Brasil, possuindo uma grande importância social e econômica para a população dessa região (OLIVEIRA et al, 2012).…”
Section: Introductionunclassified